N-doped carbon coated NiCo2S4 hollow nanotube as bifunctional electrocatalyst for overall water splitting. (April 2019) - Li, Fang; Xu, Rongchen; Li, Yueming; Liang, Fei; Zhang, Dafeng; Fu, Wen-Fu; Lv, Xiao-Jun
Abstract: Great attention has been focused on exploration of noble-metal free electrocatalysts to enable electrochemical water splitting for the process of the electricity-to-hydrogen energy conversion. The NiCo based catalyst (NiCo2 S4 ) contains the redox couples of Co 3+ /Co 2+ and Ni 3+ /Ni 2+ which are effective active centers for HER and OER, however, the high overpotential, delayed dynamics and inferior stability suppress their whole water splitting activity and stability application. Herein, N-doped carbon layer coated NiCo2 S4 hollow nanotubes (NCT-NiCo2 S4 ) were prepared by simple solvothermal method using polyacrylonitrite (PAN) as template. The carbon layer coated hollow nanotube structure not only maximized the catalytic active sites, facilitated mass transfer rate but also protected from electrolyte corrosion to improve the activity and stability. The optimized catalyst presented low overpotentials of 295 and 330 mV to drive the 100 mA cm −2 for HER and OER, respectively, meanwhile maintaining the remarkable stability. The small Tafel slope also reflects the high electrocatalytic reaction kinetic for HER and OER. When assembled in an electrolyzer as catalyst for water splitting, it only needs a cell voltage of 1.6 V at current density of 10 mA cm −2 . This work sheds some light on the rational design of functional materials for energy chemistry. Graphical abstract: Great attention has been focused on exploration of noble-metal free electrocatalysts to enable electrochemical water splitting for the process of the electricity-to-hydrogen energy conversion. The NiCo based catalyst (NiCo2S4) contains the redox couples of Co3+/Co2+ and Ni3+/Ni2+ which are effective active centers for HER and OER, however, the high overpotential, delayed dynamics and inferior stability suppress their whole water splitting activity and long time application. Herein, N-doped carbon layer coated NiCo2S4 hollow nanotubes (NCT-NiCo2S4) were synthesized by simple solvothermal method using polyacrylonitrite (PAN) as template. The carbon layer coated hollow nanotube structure not only maximized the catalytic active sites, facilitated mass transfer rate but also protected from electrolyte corrosion to improve the activity and stability. The optimized catalyst presented low overpotentials of 295 and 330 mV to drive the 100 mA cm−2 for HER and OER, respectively, meanwhile maintaining the remarkable stability. The small Tafel slop also reflects the high electrocatalytic reaction kinetic for HER and OER. When assembled in an electrolyzer as catalyst for water splitting, it only needs a cell voltage of 1.6 V at current density of 10 mA cm−2. This work sheds some light on the rational designing of functional materials for energy chemistry. Image 1